Sulfolobus islandicus meta‐populations in Yellowstone National Park hot springs. (22nd June 2017) - Campbell, Kate M.; Kouris, Angela; England, Whitney; Anderson, Rika E.; McCleskey, R. Blaine; Nordstrom, D. Kirk; Whitaker, Rachel J.
Summary: Abiotic and biotic forces shape the structure and evolution of microbial populations. We investigated forces that shape the spatial and temporal population structure of Sulfolobus islandicus by comparing geochemical and molecular analysis from seven hot springs in five regions sampled over 3 years in Yellowstone National Park. Through deep amplicon sequencing, we uncovered 148 unique alleles at two loci whose relative frequency provides clear evidence for independent populations in different hot springs. Although geography controls regional geochemical composition and population differentiation, temporal changes in population were not explained by corresponding variation in geochemistry. The data suggest that the influence of extinction, bottleneck events and/or selective sweeps within a spring and low migration between springs shape these populations. We suggest that hydrologic events such as storm events and surface snowmelt runoff destabilize smaller hot spring environments with smaller populations and result in high variation in the S. islandicus population over time. Therefore, physical abiotic features such as hot spring size and position in the landscape are important factors shaping the stability and diversity of the S. islandicus meta‐population within Yellowstone National Park.